Javanese-English Song Lyrics Translation: Kartonyono Medot Janji as a Case Study - Mukminin, Muhamad Saiful (Abjad Journal of Humanities & Education, 2024)
The present research aims to identify the translation techniques, methods, and ideologies used in translating Javanese-English for the lyrics of the song Kartonyono Medot Janji, performed by Denny Caknan. The song was re-sung in English by Hernanda Yona under the title Kartonyono Ruins Faith. The research method employed is descriptive qualitative with a translation-as-product approach. Data was collected by listening to both versions of the song in Javanese and English and then transcribed into written form. Data analysis includes data reduction, presentation, and conclusion drawing. The results show that in translating the lyrics of Kartonyono Medot Janji, the translator applied nine translation techniques: variation, established equivalence, modulation, borrowing, discursive creation, transposition, amplification, adaptation, and compensation. Based on the translation techniques used, it is evident that the translator’s method and ideology for translating the song lyrics are oriented towards the target language with a domestication ideology. The present research enhances the understanding of how translation techniques, methods, and ideology are applied to adapt song lyrics. It provides insights into how these approaches impact the translation process from Javanese to English. The present research offers a comparative linguistic analysis between Javanese and English, particularly regarding how meaning and language structure interact in translation.